Pengaruh Kepuasan Pasien Pada Kualitas Layanan Rawat Inap Terhadap Niat Discharge Against Medical Advice (Dama) (Studi di Rumah Sakit Umum Daerah Pare Kabupaten Kediri) - Satriyono, Gandung; Kristanti, Desi (Universitas Kadiri, 2018)
The purpose of this study was to analyze patient satisfaction on the quality of inpatient services to DAMA (Discharge Against Medical Advice) intentions in the Pare District General Hospital of Kediri Regency. The results of the analysis of physician interaction quality data obtained significance values (P = 0.018 <α = 0.05), with the physician attitude indicator of significance value (P = 0.694> α = 0.05); indicator of physician behavior (P = 0.002 <α = 0.05); indicator of physician expertise (P = 0.027 <α = 0.05). Thus the quality of the doctor's interaction influences the patient's intention to go home. The results of data analysis on the quality of nurse interaction (P = 0.040 <α = 0.05) with indicators of nurse attitudes (P = 0.179> α = 0.05), indicators of nurse behavior (P = 0.023 <α = 0.05), indicators of expertise nurses (P = 0.034 <α = 0.05. Thus the quality of the interaction of nurses affects the intention of the patient to go home. The results of the influence of physical environmental quality on the patient's intention to go home forced (P = 0.177> α = 0.05), thus the quality The environment does not affect the intention of the patient to go home forced.The results of the effect of the quality of the results on the patient's intention to go home forcibly (P = 0.266> α = 0.05) Thus the quality of the results does not affect the patient's intention to go home. Tujuan Penelitian ini adalah menganalisis kepuasan pasien pada kualitas layanan rawat inap terhadap niat DAMA (Discharge Against Medical Advice) di Rumah Sakit Umum Daerah Pare Kabupaten Kediri. Hasil analisis data kualitas interaksi dokter diperoleh nilai signifikansi (P = 0,018 < α = 0,05), dengan indikator sikap dokter nilai signifikansi (P = 0,694 > α = 0,05); indikator perilaku dokter (P = 0,002 < α = 0,05); indikator keahlian dokter (P = 0,027 < α = 0,05). Dengan demikian kualitas interaksi dokter berpengaruh terhadap niat pasien pulang paksa. Hasil analisis data kualitas interaksi perawat (P = 0,040 < α = 0,05) dengan indikator sikap perawat (P = 0,179 > α = 0,05), indikator perilaku perawat (P = 0,023 < α = 0,05), indikator keahlian perawat (P = 0,034 < α = 0,05. Dengan demikian kualitas interaksi perawat berpengaruh terhadap niat pasien pulang paksa. Hasil pengaruh kualitas lingkungan fisik terhadap niat pasien untuk pulang paksa (P = 0,177 > α = 0,05), dengan demikian kualitas lingkungan tidak berpengaruh terhadap niat pasien untuk pulang paksa. Hasil pengaruh kualitas hasil terhadap niat pasien untuk pulang paksa (P = 0,266 > α = 0,05). Dengan demikian kualitas hasil tidak berpengaruh terhadap niat pasien pulang paksa.